Temporal variation of selected soil fertility indicators under organic amendments in contrasting soils - Nisa, Noosrat Jahan; Santa, Sanjida Sultana; Akter, Suma; Khan, Md Harunor Rashid (Bangladesh Journal of Scientific and Industrial Research, 2025)
A laboratory incubation study (March to June 2021) was conducted to evaluate the effects of alternating wetting–drying cycles on soil properties using an acid soil from Dinajpur, a calcareous soil from Faridpur, and their 1:1 mixture. Three organic amendments such as vermicompost, tricho-compost, and burnt poultry litter were applied at 5 and 10 t ha⁻¹. The experiment was set up using a completely randomized design (CRD) with three replicates and monitored changes over 90 days. Organic fertilizers significantly (p ≤ 0.05) improved soil chemical properties. In the acid soil, pH increased from 5.42 to 7.09; in the calcareous soil, pH decreased from 8.01 to 7.43, while the 1:1 mixture maintained an intermediate, balanced pH. Electrical conductivity (EC) in the acid soil increased significantly (p ≤ 0.05) from 22.5 to 58.73 µS cm⁻¹ after 15 days of incubation. In the calcareous soil, EC rose from 70.2 to 216.83 µS cm⁻¹ by the 15 days and declined after day 30. Organic carbon in fertilizer-treated soils peaked at day 45 and then gradually decreased. Cation exchange capacity (CEC) increased significantly (p ≤ 0.05) throughout the 90 days of wetting and drying cycles. The combined influence of soil type and organic inputs showed synergistic benefits. These results highlight the potential of integrating locally available organic fertilizers to improve soil health and support sustainable agriculture, the prime need to the present world. Bangladesh J. Sci. Ind. Res. 60(4), 297-306, 2025